Development of InDels markers for the identification of cytoplasmic male sterility in Sorghum by complete chloroplast genome sequences analysis - Choe, Myeong-Eun; Kim, Ji-Young; Syed Nabi, Rizwana Begum; Han, Sang-Ik; Cho, Kwang-Soo (Frontiers in Plant Science, 2023)
Cytoplasmic male sterility (CMS) is predominantly used for F1 hybrid breeding and seed production in Sorghum. DNA markers to distinguish between normal fertile (CMS-N) and sterile (CMS-S) male cytoplasm can facilitate F1 hybrid cultivar development in Sorghum breeding programs. In this study, the complete chloroplast (cp) genome sequences of CMS-S and Korean Sorghum cultivars were obtained using next-generation sequencing. The de novo assembled genome size of ATx623, the CMS-S line of the chloroplast, was 140,644bp. When compared to the CMS-S and CMS-N cp genomes, 19 single nucleotide polymorphisms (SNPs) and 142 insertions and deletions (InDels) were identified, which can be used for marker development for breeding, population genetics, and evolution studies. Two InDel markers with sizes greater than 20 bp were developed to distinguish cytotypes based on the copy number variation of lengths as 28 and 22 bp tandem repeats, respectively. Using the newly developed InDel markers with five pairs of CMS-S and their near isogenic maintainer line, we were able to easily identify their respective cytotypes. The InDel markers were further examined and applied to 1,104 plants from six Korean Sorghum cultivars to identify variant cytotypes. Additionally, the phylogenetic analysis of seven Sorghum species with complete cp genome sequences, including wild species, indicated that CMS-S and CMS-N contained Milo and Kafir cytotypes that might be hybridized from S. propinquum and S. sudanese, respectively. This study can facilitate F1 hybrid cultivar development by providing breeders with reliable tools for marker-assisted selection to breed desirable Sorghum varieties.